DDX56 inhibits PRV replication through regulation of IFN-β signaling pathway by targeting cGAS - Xie, Jingying; Li, Xiangrong; Yang, Shunyu; Yan, Zhenfang; Chen, Lei; Yang, Yanmei; Li, Dianyu; Zhang, Xiangbo; Feng, Ruofei (Frontiers in Microbiology, 2022)
Pseudorabies virus (PRV) is an agent of Aujeszky's disease, and causes great economic losses to pig farming. Re-outburst of pseudorabies implies that new control measures are urgently needed. We show here that DDX56 possesses the ability to inhibit PRV replication in vitro, which may be an important factor for PRV infection. Overexpression of DDX56 inhibited PRV genomic DNA transcription and lower titers of PRV infection in PK15 cells, whereas down-regulation of the DDX56 expression had a promotion role on virus replication. Further study demonstrated that DDX56 exerted its proliferation-inhibitory effects of PRV through up-regulating cGAS-STING-induced IFN-β expression. Moreover, we found that DDX56 could promote cGAS expression and direct interaction also existed between DDX56 and cGAS. Based on this, DDX56-regulated IFN-β pathway may be targeted at cGAS. To verify this, down-regulated cGAS expression in DDX56 over-expression cells was performed. Results indicated that knockdown of cGAS expression could abrogate the inhibition role of DDX56 on PRV proliferation and weaken the effect of DDX56 on IFN-β expression. In addition, DDX56 played a promotion role in IRF3 phosphorylation and nucleus translocation. Altogether, our results highlight DDX56's antiviral role in PRV infection, and our findings contribute to a better understanding of host factors controlling PRV replication.